An easy death [compact disc, unabridged] - Harris, Charlaine (Harris, Charlaine. Gunnie Rose., 2018)
Gunnie Lizbeth Rose has been hired by a pair of Russian sorcerers as both their local guide and muscle through the small towns of East Texas as they search for a distant relative of an infamous sorcerer, Rasputin, whose bloodline can help save their emperor-in-exile as an ever-increasing number of assassins tries to stop them. Time is middle 20th century.